Transculturalism beyond dualism: in memory of Rudolf Wagner - Sax, William Sturman (The journal of transcultural studies, 2021)
In this paper, I summarize and critique one of Rudolf Wagner’s last public lectures, delivered in November 2018 and entitled “Of Trees and the Wood, Cultures and CULTURE.” In his lecture, Wagner summarized and amplified certain critiques of the culture concept and, inspired by Peter Wohlleben’s book The Hidden Life of Trees, made some suggestions about how a “non-binary” notion of culture might be developed. In my commentary, I summarize parallel critiques of the culture concept from within anthropology, and relate Wagner’s discussion of Wohlleben to wider currents in what is called “post-humanism.”